Dental Treatment for the Pregnant Patient - Fagoni, Thalita Guarda; Vasconcelos, Rafaela Andrade de; Cardoso, Paula Elaine; Gomes, Ana Paula Martins; Camargo, Carlos Henrique Ribeiro; Gonçalves, Simone Helena Ferreira (Brazilian Dental Science, 2014)
Dental treatment of pregnant women should be accomplished with safety. Consequently, the dental professional should evaluate its real need and risks for the mother and the baby. This paper reports, through a literature review, the caution with the clinical dental procedures commonly performed and possible risks of the therapeutic agents used, allowing the dentist to evaluate the treatment and the drug to be administered to the pregnant women.